2015
DOI: 10.1155/2015/742419
|View full text |Cite
|
Sign up to set email alerts
|

The Rarest of the Rare: Crossed Fused Renal Ectopia of the Superior Ectopia Type

Abstract: Crossed fused renal ectopia is a rare congenital anomaly of the urinary system where one kidney crosses over to opposite side and the parenchyma of the two kidneys fuse. Herein, we present an atypical CFRE case whose renal anatomy does not exactly match any of the already defined CFRE types. Both of the kidneys are ectopic with the crossed ectopic right kidney lying superiorly and fused to the upper pole of the left kidney. Renal arteries were originating from the common iliac arteries. A focal 90% stenosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 5 publications
(8 reference statements)
0
24
0
1
Order By: Relevance
“…Resulting from aberrant migration and crossing of the midline of the metanephric blastema and ureteral bud, CFRE is thought to develop during 4 th to 8 th weeks of gestation. Mostly remaining asymptomatic and detected as an incidental finding during imaging studies, six well-defined anatomical variations of CFRE have been reported [2]. We report here one such case of crossed fused renal ectopia detected by usg, which was later on confirmed by computed tomography Keywords: CFRE; MDCT; Hydronephrosis …”
Section: Introductionmentioning
confidence: 85%
“…Resulting from aberrant migration and crossing of the midline of the metanephric blastema and ureteral bud, CFRE is thought to develop during 4 th to 8 th weeks of gestation. Mostly remaining asymptomatic and detected as an incidental finding during imaging studies, six well-defined anatomical variations of CFRE have been reported [2]. We report here one such case of crossed fused renal ectopia detected by usg, which was later on confirmed by computed tomography Keywords: CFRE; MDCT; Hydronephrosis …”
Section: Introductionmentioning
confidence: 85%
“…Crossed renal ectopia is a rare entity detected incidentally in 20 to 30% of cases [ 4 ] and results from the aberrant migration and crossing of the midline by the metanephric blastema and the ureteral bud [ 5 ], usually occurring during the fourth to eighth week of gestation [ 5 ]. Despite the ectopic position of the kidneys, the ureters are not crossed and insert normally into the bladder [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second in incidence after horse-shoe kidney [ 5 ], with male-to-female predominance of 1.4 to 2 : 1, with two to three times higher chance to have a left-to-right ectopy [ 7 ], CRE is further categorized into four subcategories: crossed fused renal ectopia (CFRE), unfused ectopia, solitary CRE, and unfused bilateral CRE [ 4 ]. Among the four subcategories, those with fusion represent the majority of cases, around 90% [ 4 ], with an incidence of 1 in 2000 [ 6 ], followed by the unfused form with an incidence of 1 : 75000 [ 5 ]. There are 6 subtypes of CFRE: inferior, sigmoid or S-shaped, lump, disc, L-shaped, and superior CRFE [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature on cross-fused renal ectopia consists of case reports. 3 , 4 Its overall prevalence is estimated to be 1 in 900 live births. 5 This congenital renal abnormality in conjunction with a renal mass is even more uncommon.…”
Section: Discussionmentioning
confidence: 99%